A PROSPECTIVE EVALUATION OF BREAST SATISFACTION AND EXPECTATION IN PREOPERATIVE BREAST RECONSTRUCTION PATIENTS - Kuroda, Flávia; Urban, Cicero Andrade; Loureiro, Marcelo Paula; Lourenço, Mateus Ricardo Ulsan; Sobreiro, Bernardo Passos (Mastology, 2021)
Introduction: There is a consensus that breast reconstruction makes an important positive contribution to the quality of life of breast cancer patients. However, a large proportion of breast cancer survivors have unmet expectations surrounding reconstruction after mastectomy, particularly in relation to appearance. Approximately 40% of women who underwent breast reconstruction after mastectomy reported their reconstruction to be worse than expected. There is little consensus about what impact specific factors have on women`s satisfaction with breast reconstruction process and outcomes. Objectives: To delineate factors affecting preoperative native breast satisfaction and expectation with the surgery using the BREAST-Q in patients prior to oncological breast surgery following breast reconstruction. Methods: A prospective cross-sectional trial with breast cancer patients enrolled from November 2019 to December 2020 at Hospital Nossa Senhora das Graças Breast Unit in Curitiba, Brazil. Two independent groups were studied. The first group included patients who underwent mastectomy following immediate breast reconstruction (IBR) with implant. The second group underwent breast-conserving therapy (BCT) following level 2 oncoplastic techniques. This study was approved by the Internal Review Boad of Positivo University, Curitiba, Brazil. All patients were invited to complete a patient-reported outcome (BREAST-Q) Expectations Module and Pre-operative Breast reconstruction module prior to surgery. Results: Overall, seventy-nine patients with breast cancer completed the preoperative BREAST-Q. Patients were divided into BCT following oncoplastic surgery (n=49) and mastectomy following IBR with implant (n=30) groups. The mastectomy with IBR implants group had better satisfaction with their native breast than BCT oncoplastic group. Comparing Breast-Q expectations rate, women in BCT following oncoplastic group had higher expectations for breast appearance when clothed than the group of mastectomy with IBR implant. Previous aesthetic breast surgery and neoadjuvant chemotherapy were significant predictors of preoperative physical well-being. Younger age was significantly correlated with pain expectation in the surgery. Patients who were fifty years old or more and had a university or higher education level expected that the breast appearance would match almost as well as the same ten years after. Conclusions:This study results highlight the need to improve education and informed decision-making about breast reconstruction. Patients demonstrated to have high expectations for breast appearance after reconstruction and expect not to change over time. Understanding which factors affect patient’s satisfaction with native breasts and their expectation with the surgery in the preoperative set could improve preoperative counseling and the management of patient’s expectations of subsequent breast reconstruction.